Knowledge, Attitude, Behavior, and Stress Related to COVID-19 among Undergraduate Health Care Students in Jordan - Mustafa, Ruba M.; Alrabadi, Nasr N.; Alshali, Ruwaida Z.; Khader, Yousef S.; Ahmad, Dana M. (European Journal of Dentistry, 2020)
Objectives This study aimed to assess knowledge, attitude, and infection control measures related to the coronavirus disease 2019 (COVID-19) pandemic outbreak among Jordanian health care students. Besides, their social behavior and stress level regarding COVID-19 infection were assessed.Materials and Methods An online questionnaire was distributed to medical, dental, pharmacy, nursing, and applied health science students in Jordan during the COVID-19 outbreak quarantine in March 2020. The questionnaire comprised 38 questions assessing demographic data, knowledge, attitude, risk perception, and stress level toward COVID-19. Questions regarding infection control measures and social behavior after the quarantine were also included.Statistical Analysis Independent samples t-test, one-way analysis of variance (ANOVA), and chi-square at a significance level of 5% were used for data analysis.Results A total number of 935 responses were collected. The knowledge score of 55.72% of participants was satisfactory and it was higher for the clinical years’ students compared with the basic years’ students (p = 0.000) (descending order: sixth year > fifth year > fourth year > third year > first year > second year). Also, knowledge scores were significantly higher for medical and dental students than other disciplines (descending order: medicine, dentistry, pharmacy, nursing/applied) (p = 0.000). The social media (89.1%) and TV or radio (69.5%) were mainly routes through which participants heard about COVID-19. Moderate and justifiable feelings about COVID-19 were found in the majority of the participants.Conclusion Although the majority of students showed good knowledge scores, few of them appeared to have a serious lack of knowledge. Therefore, proper education and mentoring are necessary for students before reopening the university campuses.
Keywords: attitude; COVID-19; infection control; knowledge; students